2011
DOI: 10.1002/pbc.23086
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial ependymoma in children: To observe or to treat following gross total resection?

Abstract: BackgroundThe standard treatment for ependymoma is surgical resection followed by postoperative irradiation to the local site. The role of radiation therapy in completely resected supratentorial ependymoma has been questioned over the past two decades.ProcedureRetrospective review of the medical records of all consecutively diagnosed supratentorial ependymoma patients at Children's Hospital Los Angeles between January 1999 and December 2009.ResultsTen patients (three females) were included. The median age at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…However, the importance of a complete resection varies between the tumour types. A complete macroscopic resection is highly prognostic for ependymomas [1,2], whereas small amounts of residual medulloblastoma (up to 1.5cm 2 ) are not of prognostic significance if treated with radiotherapy and chemotherapy [3] and small residual masses of pilocytic astrocytoma may be observed without further treatment [4]. Histopathology is usually not available for several days after the operation and intraoperative histopathology is commonly used to inform the surgeons of the likely tumour type but the techniques available are not accurate [5] and this strategy does not allow patient-specific clinical management planning prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the importance of a complete resection varies between the tumour types. A complete macroscopic resection is highly prognostic for ependymomas [1,2], whereas small amounts of residual medulloblastoma (up to 1.5cm 2 ) are not of prognostic significance if treated with radiotherapy and chemotherapy [3] and small residual masses of pilocytic astrocytoma may be observed without further treatment [4]. Histopathology is usually not available for several days after the operation and intraoperative histopathology is commonly used to inform the surgeons of the likely tumour type but the techniques available are not accurate [5] and this strategy does not allow patient-specific clinical management planning prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in this study 4 relapses were observed, 2 of them in patients who had undergone initial gross total resection. Similarly to our case, there were 5 relapses, and 3 of those patients had had a prior gross total tumor excision [3]. We believe that even after complete excision there is a risk of tumor recurrence and for that reason a close follow-up is needed.…”
mentioning
confidence: 99%
“…We agree with Tanaka et al that gross total excision should be the goal of surgery and this is related to a better outcome. Recently, Venkatramani et al [3] have also reported that surgery alone may be an acceptable treatment option in completely resected supratentorial ependymoma. Nevertheless, in this study 4 relapses were observed, 2 of them in patients who had undergone initial gross total resection.…”
mentioning
confidence: 99%
“…A opção por seguimento sem radioterapia é aceitável nos pacientes com ressecção completa, grau histológico não anaplásico, localização medular ou supratentorial e em crianças menores de 3 anos, reservando-se a radioterapia para casos com progressão da doença (Sgouros, Malluci et al 1996;Schwartz and McCormick 2000;Little, Sheean et al 2009;Sung, Lim do et al 2012;Venkatramani, Dhall et al 2012;Wright and Gajjar 2012).…”
Section: Radioterapiaunclassified
“…A sobrevida em cinco anos em crianças com tumores ressecados totalmente é de 67 a 80%, enquanto que os com ressecção incompleta é de 22 a 47%. Semelhantemente, o tempo livre de progressão em cinco anos é maior nos casos de ressecção completa (51 a 75%) do que nos de ressecção incompleta (0 a 26%) (Nazar, Hoffman et al 1990;Healey, Barnes et al 1991;Rousseau, Habrand et al 1994;Pollack, Gerszten et al 1995;Foreman, Love et al 1996;Needle, Goldwein et al 1997;Perilongo, Massimino et al 1997;Robertson, Zeltzer et al 1998;Horn, Heideman et al 1999;Figarella-Branger, Civatte et al 2000;Palma, Celli et al 2000;Paulino, Wen et al 2002;van Veelen-Vincent, PierreKahn et al 2002;Zamecnik, Snuderl et al 2003;Kawabata, Takahashi et al 2005;Shu, Sall et al 2007;Tihan, Zhou et al 2008;Merchant, Li et al 2009;Benesch, Weber-Mzell et al 2010;Venkatramani, Dhall et al 2012).…”
Section: Extensão Da Ressecçãounclassified